Implementasi Sistem Raport Digital Madrasah Berbasis Web di Ma Al-Mubarokah Banyuasin - Ibrahim Baim; Choirun Niswah; Rohmah Safitri (Indo-MathEdu Intellectuals Journal, 2023)
This research aims to understand how the implementation of a web-based digital school report system in Ma Al-Mubarokah Banyuasin madrasah works. The research object consists of three stages: (1) Pre-Implementation Stage, (2) Implementation Stage, and (3) Evaluation Reporting Stage. This study follows a qualitative descriptive research approach, with a research group of 12 participants including the school principal, deputy principal in charge of the curriculum, educational staff, and teaching staff. Data is collected through three methods: interviews, observations, and documentation. The data analysis technique involves data collection, data presentation, and data verification. The research findings indicate that: (1) The Pre-Implementation Stage involves tasks such as registration, enrollment, creating madrasah accounts, and teacher accounts for the implementation of the web-based digital school report system. (2) The Implementation Stage shows successful collaboration between operators, teachers, and class guardians, supported by the school principal, resulting in a smooth implementation process. (3) The Evaluation Reporting Stage involves holding meetings to evaluate and improve the web-based digital school report system